Hybrid intelligent systems : 18th International Conference on Hybrid Intelligent Systems (HIS 2018) held in Porto, Portugal, December 13-15, 2018 /: 18th International Conference on Hybrid Intelligent Systems (HIS 2018) held in Porto, Portugal, December 13-15, 2018. ([2020]) - Unknown
No abstract available